실내 승마운동이 고령자의 기초체력 및 ADL 기능에 미치는 효과 - 김의령; 강승록; 유창호; 문동안; 박상용; 권대규; Kim, E.R; Kang, S.R; Yu, C.H; Moon, D.A; Park, S.Y; Kwon, T.K (Journal of biomedical engineering research, 2013)
The purpose of this study was to verify exercise effect of horse riding exercise according to estimate basal physical fitness and activities of daily living(ADL) function in the aged. Participants were nineteen peoples who have no impediment of activity. They performed horse riding exercise using SRider(Neipplus, Co., Korea) at sixty minutes a day. Exercise has progressed three days a week for eight weeks. We measured trunk flexion, sit up, whole body reaction, leg strength and maximal oxygen uptake as basal physical fitness. Also three meter gait, single stance with eyes opened and single stance with eyes closed as ADL function were estimated once a month. The result of legs strength and whole body reaction showed the higher significantly than before the exercise. Moreover, the result of three meter walking ability only increased significantly among the ADL function. This means that horse riding exercise might be activated continuous muscular contraction with maintained tonus of muscle. We thought that continuous movement of horse riding could be lead to isometric muscle contraction in lower limbs. Our study found that horse riding exercise could improve lower strengths and muscle reaction for exercise effect. Also we suggested that horse riding exercise could be adapted to exercise methods that could provide rehabilitation and treatment enough for the aged or disabled person.